Healing Space: The Synaesthetic Quality of Church Architecture - Daelemans, Bert (Religions, 2020)
There is a growing literature on the healing effects of buildings designed for healthcare, but publications that insist on this spiritual and healing dimension in church architecture are rare. Contemporary ecclesial buildings are often rightly criticized for their cold and soulless emptiness. However, through the analysis of four emblematic case studies, this article aims to lay bare an essential dimension of architecture that is often overlooked, a multisensory and synaesthetic dimension that engages our body even before we become aware of it. Hence, this article builds upon the recurrent plea of spatial theorists, philosophers, and architects for synaesthetic space as a reaction to a dominant ocularcentric environment. Surprisingly, contemporary church architecture seems rather propitious to deploy this inherently religious dimension that is at once healing and spiritual in a new sense, which is especially needed nowadays.